Políticas culturais e redes sociotécnicas: reconfigurando o espaço público - Marco Antonio de Almeida (Ciências Sociais Unisinos)
The objective of this work is to analyze, from the perspective of cultural mediation and information based on the use of Information and Communication Technologies (ICT), some experiences of Brazilian cultural policies. In terms of methodology, we start from a brief theoretical discussion, then analyze documents of the Ministry of Culture and IPEA, as well as interviews with some actors involved in the processes of developing and imple- menting these policies. We also analyze two micro-case studies of cultural activities and social networks related to culture themes. Preliminary findings indicate that the degree of autonomy and the sociocultural conditions given for the appropriation of information and the uses of technologies vary contextually. While it is still premature to speak of a “democratization” of access to cultural information and new practices of users, it is clear, on the other hand, that the present technocultural process points toward unprecedented and promising possibilities.